Alarming Rate of “Yahoo Plus” and Human Insecurity Dilemma in Nigeria: Implication for Counselling - lawani, Comfort; Osagie-Obazee, Gloria (European Scientific Journal, ESJ, 2019)
The daily surge of cyber fraudsters popularly known as yahoo–boys which has often resulted in the loss of lives of their victims has become a new wave making round in Nigeria today. This study, therefore, seeks to unravel the nexus between the alarming rate of cyber fraudsters (yahoo-boys) and Human Insecurity Dilemma, with its corresponding implication(s) for safety and security counselling. Thirty (30) repentant yahoo boys were interviewed from the 3 states out of the 6 Geo-political zones in the country. The study employed the descriptive survey design approach. The instrument used for data collection was a structured interview with a reliability coefficient of 0.87 while the data collected were analysed using the non parametric test known as Kruskal Wallis Statistical Technique. The result revealed that some of the yahoo boys use human parts, sanitary pad, women undies and gifts, either to their parents or to their loved friends, which will serve as a contact point for money making rituals. Based on these findings, the researchers drew a caveat on the implication of taking counselling for safety and security seriously in all the states in the country, and among other things, recommends a serious awareness campaigns in all parts of the country on the negative implication(s) of the yahoo-boys activities.